Pengaruh Label Halal dan Wom (Word Of Mouth) Terhadap Keputusan Pembelian Pada UMKM Sambal Petis Mbak Emil Di Kabupaten Tuban - Moch Vicky Sandhika Pratama (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The inclusion of a halal label is important not only for consumers but also for producers. Having halal certification for a product is a source of reassurance for consumers who are still unsure about the halalness of the product. Based on observations, Mbak Emil's Sambal Petis already has a halal label but has not yet been displayed by the public through media. This research aims to test whether halal labels and word of mouth influence purchasing decisions. The type of research used is quantitative research. Data collection techniques use primary data through questionnaires. The population of this research is consumers of Mbak Emil's Sambal Petis. The sample method used is non-probability sampling. The number of respondents used as a sample was 45 sample respondents using the formula number of samples = number of indicators x (5 to 10) as the multiplier. Data analysis uses questionnaire tests, descriptive analysis, classical assumption tests, multiple regression analysis, heteroscedasticity tests, determinant analysis and hypothesis testing. The results of this research show that the halal label, word of mouth has a positive effect on purchasing decisions for Mbak Emil's Sambal Petis product partially and simultaneously with a strong contribution. The conclusion of this research is that there is a relationship between the halal label and word of mouth which has a positive influence on the decision to purchase Mbak Emil's Sambal Petis product, then for suggestions through the inclusion of the halal label and word of mouth and because of the stories or information submitted by other consumers and recommendations from other people. correctly, can influence consumer purchasing decisions.